Enhancement in Biological Availability of Vitamins by Nano-engineering and its Applications: An Update - Mishra, Sadhna; Sahani, Shalini; Pandhi, Shikha; Kumar, Arvind; Mahato, Dipendra K.; Kumar, Pradeep; Khaire, Kaustubh Chandrakant; Rai, Ashutosh (Current Pharmaceutical Biotechnology, 2024)
Vitamin nano-engineering has been accomplished by synthesizing various nanostructures to improve their stability, bioavailability, shelf life, and functioning. This review provides a detailed description of recent advances in the art of encapsulation with high efficiency through the use of practical and logistic nano-engineering techniques such as nanofibres, nanogels, nanobeads, nanotubes, nanoparticles, nanoliposomes, and many other nanostructures. To demonstrate the interaction of molecules with nano-forms, the bioavailability of several vitamins such as B, C, E, A, D, and others in the form of nanostructures is explored. This review will provide a thorough understanding of how to improve bioavailability and nanostructure selection to extend the utility, shelf life, and structural stability of vitamins. While nanoencapsulation can improve vitamin stability and distribution, the materials employed in nanotechnologies may offer concerns if they are not sufficiently tested for safety. If nanoparticles are not adequately designed and evaluated, they may cause inflammation, oxidative stress, or other unwanted effects. Researchers and makers of nanomaterials and medication delivery systems should adhere to established rules and regulations. Furthermore, long-term studies are required to monitor any negative consequences that may result from the use of nanostructure.
Keywords: lipid matrix